2018
DOI: 10.3892/ol.2018.7725
|View full text |Cite
|
Sign up to set email alerts
|

TGFBR1*6A is a potential modifier of migration and invasion in colorectal cancer cells

Abstract: Abstract. Type 1 transforming growth factor β receptor (TGFBR1)*6A, a common hypomorphic variant of TGFBR1, may act as a susceptibility allele in colorectal cancer. However, the contribution of TGFBR1*6A to colorectal cancer development is largely unknown. To test the hypothesis that TGFBR1*6A promotes colorectal cancer invasion and metastasis via Smad-independent transforming growth factor-β (TGF-β) signaling, the effect of TGFBR1*6A on the invasion of colorectal cancer cells was assessed. pCMV5-TGFBR1*6A-HA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Identified mutations in TGFBR1 in CRC cell lines are not common [50]. TGFBR1*6A, a polymorphic allele of TGFBR1 , was detected in the TGFBR1 tumor-specific mutations [51]. TGFBR1*6A has been associated with a 24% increase in the risk of CRC [28, 51].…”
Section: Mutations In the Components Of Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Identified mutations in TGFBR1 in CRC cell lines are not common [50]. TGFBR1*6A, a polymorphic allele of TGFBR1 , was detected in the TGFBR1 tumor-specific mutations [51]. TGFBR1*6A has been associated with a 24% increase in the risk of CRC [28, 51].…”
Section: Mutations In the Components Of Signaling Pathwaysmentioning
confidence: 99%
“…TGFBR1*6A, a polymorphic allele of TGFBR1 , was detected in the TGFBR1 tumor-specific mutations [51]. TGFBR1*6A has been associated with a 24% increase in the risk of CRC [28, 51]. It is speculated that TGFBR1*6A may cause switching of TGF-β growth inhibitory signals to the growth stimulatory ones, thereby contributing to tumorigenesis [51].…”
Section: Mutations In the Components Of Signaling Pathwaysmentioning
confidence: 99%
“…For example, loss of three alanine residues within a stretch of nine alanine residues in the N-terminal region of TβRI (TGFBR1*6A) was associated with an increased risk of CRC [122], though these results have not been confirmed [123]. However, a recent study pointed out an oncogenic property of TGFBR1*6A which may promote the migration and invasion of colorectal cancer cells [124].…”
Section: Role Of Tgf-β Signal In Gastrointestinal Cancersmentioning
confidence: 99%
“…Experimental studies have shown that TGFBR1 can promote malignant proliferation and metastasis of tumors by regulating epithelial‐mesenchymal transformation . Rosman et al and Zhou et al also revealed similar outcomes that TGFBR1*6A could promote the invasion and metastasis of MCF‑7 breast cancer cells and colorectal cancer cells. Moreover, Nicoloso et al demonstrated that GG genotype of rs334348 was associated with lower TGFBR1 expression .…”
Section: Discussionmentioning
confidence: 80%
“…This pathway is vital in the development and progression of malignancy by regulating cellular proliferation and differentiation . Previous researches have shown that genetic polymorphism and aberrant expression of TGFBR1 were associated with prognosis of several digestive tract cancers, including gastric cancer and colorectal cancer . Additionally, a recent study also demonstrated that higher TGFBR1 expression may represent poor prognosis in advanced head and neck squamous cell carcinomas (HNSCC) .…”
Section: Introductionmentioning
confidence: 99%